Ecological features of environmental factors Kyiv - Аксьонов, О.О. (Proceedings of National Aviation University (archive), 2008)
The data of ecological crisis probability increase am a “dense” city are given. The mast probability ecological factors simultaneous action of which creates extreme conditions for population, which are expressed through illnesses of population i.e. neurotic system, respiratory organs Immunity decrease.